Obstacles Experienced By Students In Completing The Thesis Students - Junaidi Jun; Junaidi Naidi; Vera Wardani Vera; Yulsafli Yul (UNIVERSITAS SERAMBI MEKKAH, 2022)
This study aims to and out what obstacles hinder students from the Faculty ofTeacher Training and Education at Serambi Mekkah University in preparingtheir thesis. The population of this study was students of the Faculty of TeacherTraining and Education Serambi Mekkah University, Indonesian LanguageEducation Study Program, and Physical Education Study Program in preparingtheses. This type of research is qualitative research using a descriptive approach. The method used is descriptive qualitative. The total population or research sample is 31 students. Data collection techniques through the distribution of questionnaires and direct interviews with the students concerned. Processing of data using a simple statistical formula, which uses the concept of average and percentage. To classify the research results using the assessment norm, namely the benchmark table of qualitative and quantitative percentages. Data processing is done manually and then presented in tabular form and discussed in narrative form. The results of the study show some information that final year students of the Faculty of Teacher Training and Education Serambi Mekkah University experience obstacles in the preparation of a thesis and the most dominant obstacle are the obstacle caused by the lack of facilities and infrastructure that support the completion of the thesis.